Health-Related Quality of Life in Diabetic Women: Comparing Obese & Normal weight - Alnaqeeb, Noor Shamil; Abdul Raheem, Yousif; Ali, Besmah M. (AL-Kindy College Medical Journal, 2022)
Background: The prevalence of both obesity & diabetes are increasing all over the world & more in women. They have a negative impact not only on morbidity & mortality but also on quality of life. Objectives: To assess the HRQoL with a specific comparison between obese & normal weight among women with Type 2 Diabetes Mellitus. Subjects and Methods: A cross sectional study was conducted among 618 diabetic women aged 18 to 45 years. Data collection was done by interview & SF36 questionnaire. A comparison for Physical Component Summary & Mental Component Summary scores were done on the base of their Body Mass Index. Results: There was a significant difference score between obese & normal patients in PCS (p=0.001) & in MCS (p=0.009). The normal weight patients had significantly higher PCS mean (±SD), in strata of ; age (≤35,>35)=78.43(±8.80), 65.02(±17.9) /socioeconomic status (poor, fair) =69.96(±20.72), 67.50(±15.71) /marital status (single, married, divorced or widowed)=72.50(±14.81), 67.68(±17.44), 71.09(±16.79) /number of children (≤ 2 / >2 ) =68.66(±12.91), 69.64(±20.82) /smoking (smoker , nonsmoker) =72.50(±8.55), 68.44(±17.34) / duration of DM (5-10 year, >10 year) =67.68(±16.46), 70.27(±17.18)/complications of DM (one complication , > one complications) =71.12(±15.56), 77.91(±8.98)/treatment type (OHM, injection, both) =64.86(±18.87), 73.67(±14.49), 60.00 (±10.31)& regularity of visit (poor,fair,good) =66.25(±9.78), 60.31(±19.73), 72.63(±14.00). Also the same thing in MCS mean (±SD), in strata of; (SES) (poor) =72.11(±18.82), number of children (>2) =69.20(±19.66), smoking (smoker) =82.25(±11.50), duration of DM (>10 year) =67.55(±16.3), complications of DM (> one complications) =65.81(±10.17), & regularity of visit (poor) =59.86(±18.46). Conclusions: Obese patients have a lower score as compared with normal weight patients in PCS & MCS.